1992
DOI: 10.1073/pnas.89.5.1929
|View full text |Cite
|
Sign up to set email alerts
|

Distinct hypermethylation patterns occur at altered chromosome loci in human lung and colon cancer.

Abstract: Regional increases in DNA methylation occur in normally unmethylated cytosine-rich areas in neoplastic cells. These changes could potentially alter chromatin structure to inactivate gene transcription or generate DNA instability. We now show that, in human lung and colon cancer DNA, hypermethylation of such a region consistently occurs on chromosome 17p in an area that is frequently reduced to homozygosity in both tumor types. Over the progression stages of colon neoplasia, this methylation change increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
2
1

Year Published

1994
1994
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 39 publications
4
74
2
1
Order By: Relevance
“…In a previous study of HIC1 methylation status in neural tumors, we found hypermethylation of all NotI sites in and around the region of the gene in virtually all low-and mid-grade astrocytomas but only in 50% of high grade gliomas (Makos et al, 1993a). In the present study, a range of methylation was seen in the majority of tumors ( Figure 1c) and these patterns must be put into perspective with the methylation status of HIC1 in normal brain.…”
Section: Methylation Status Of Six Cpg Island Associated Promoters Insupporting
confidence: 65%
See 3 more Smart Citations
“…In a previous study of HIC1 methylation status in neural tumors, we found hypermethylation of all NotI sites in and around the region of the gene in virtually all low-and mid-grade astrocytomas but only in 50% of high grade gliomas (Makos et al, 1993a). In the present study, a range of methylation was seen in the majority of tumors ( Figure 1c) and these patterns must be put into perspective with the methylation status of HIC1 in normal brain.…”
Section: Methylation Status Of Six Cpg Island Associated Promoters Insupporting
confidence: 65%
“…HIC1 is now known to exhibit partial methylation in normal cells in a tissue speci®c way ranging from no methylation in sites such as blood and bone marrow cells (Issa et al, 1997b), ®broblasts, skin and colon (Wales et al, 1995), to methylation of only 2 ± 3 of the most 5' NotI sites in kidney (Makos et al, 1993b) and bronchial epithelium (Vertino et al, 1993), to a most interesting pattern of 50% completely methylated and 50% unmethylated alleles in breast (Issa JPJ, unpublished observations) and prostate epithelium (Morton et al, 1996). Our present data suggest that cells of the central nervous system are also characterized by partial methylation at the HIC1 locus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas VHL and MTS-1/p16 were both initially established as tumor suppressor genes by linkage to hereditary cancers and by ®ndings of tumor speci®c somatic mutations, the HIC-1 candidate tumor suppressor gene was identi®ed by cloning of a 17p13.3 chromosomal region which contained a dense CpG island that is hypermethylated in tumor cell DNA (Makos-Wales et al, 1995). The HIC-1 gene has been found to be extensively methylated in primary glioblastomas, colon and renal cell carcinomas (Makos et al, 1992(Makos et al, , 1993a and in cell lines derived from cancers of the brain, breast, colon and lung (Makos-Wales et al, 1995). In established cell lines, this methylation has been found to be associated with transcriptional inactivation of the gene (Makos-Wales et al, 1995).…”
Section: Discussionmentioning
confidence: 99%